PUNISHMENT in ISLAMIC EDUCATION - Syahrul Hasibuan (Madania: Jurnal Ilmu-Ilmu Keislaman, 2012)
The great punishment which is followed by violence is not desired by anyone including in education institution. However, it cannot be avoided that in a education institution there is still a violence. This paper attempts to explore some points related to punishment in Islamic education. The result is that pusnishment should consider some steps and requirements which should be understood by Islamic teachers.